A bench study comparing between scalpel-bougie technique and cannula-to-Melker technique in emergency cricothyroidotomy in a porcine model - Chang, See Seong; Tong, Qian Jun; Beh, Zhi Yuen; Quek, Kelvin Howyow; Ang, Bun Hui (Korean Society of Anesthesiologists, 2018)
Background: The ideal emergency cricothyroidotomy technique remains a topic of ongoing debate. This study aimed to compare the cannula-to-Melker technique with the scalpel-bougie technique and determine whether yearly training in cricothyroidotomy techniques is sufficient for skill retention. Methods: We conducted an observational crossover bench study to compare the cannula-to-Melker with the scalpel-bougie technique in a porcine tracheal model. Twenty-eight anesthetists participated. The primary outcome was time taken for device insertion. Secondary outcomes were first-pass success rate, incidence of tracheal trauma, and technique preference. We also compared the data on outcome measures with the data obtained in a similar workshop a year ago. Results: The scalpel-bougie technique was significantly faster than the cannula-to-Melker technique for cricothyroidotomy (median time of 45.2 s vs. 101.3 s; P = 0.001). Both techniques had 100% success rate within two attempts; there were no significant differences in the first-pass success rates and incidence of tracheal wall trauma (P > 0.999 and P = 0.727, respectively) between them. The relative risks of inflicting tracheal wall trauma after a failed cricothyroidotomy attempt were 6.9 (95% CI 1.5–31.1), 2.3 (95% CI 0.3–20.7) and 3.0 (95% CI 0.3–25.9) for the scalpel-bougie, cannula-cricothyroi-dotomy, and Melker-Seldinger airway, respectively. The insertion time and incidence of tracheal wall trauma were lower when the present data were compared with data from a similar workshop conducted the previous year. Conclusions: This study supports the use of a scalpel-bougie technique for cricothyroidotomy by anesthetists and advocates a yearly training program for skill retention.